IDENTIFICATION OF CONSERVATION PRIORITY LOCATION IN INDONESIA BASED ON LAND-SEA CONNECTIVITY - Christian Novia N Handayani; Estradivar; Dirga Daniel; Oki Hadian; Khairil Fahmi Faisal; Dicky Sucipto; Puteri Maulida (COJ (Coastal and Ocean Journal), 2017)
The environment quality around those rivers and canals will affect the health of the coastal ecosystem and biota living in it. Empirically, there is an ecological connection between ecosystem in coastal areas and between coastal areas to the mainland and the high seas. Therefore, marine spatial planning should consider any change on landscape upstream. The aim of this study was to define new locations which have high conservation value based on connectivity between terrestrial and marine. The method used in this study was spatial analysis using systematic conservation planning approach with Marxan as the decision support tool. Marxan works based on scenarios developed by spatial planner. This study was using two primary scenarios: first, consider the existing protected areas; second did not consider the existing protected areas (PAs) to identify the gaps between new priority locations and the existing PAs. The data used in this study were basic spatial data, ecological data, and biodiversity data from various sources. The study area were all islands of Indonesia, devided into seven clusters. Based on those two scenarios, the result of the study shows that there are 108 locations in Indonesia which identified as areas which have high conservation value and also hold potential land-sea connection at once, inside and outside existing protected areas. Based on this study, if in the future the stakeholder have plans to do intervention in those areas primary in conservation field, those identified locations could be considered as new areas. Keywords Spatial analysis, Marxan, Conservation, Connectivity, Land-sea